An Experiment on Parameter Selection for Landslide Susceptibility Mapping using TF-IDF. (December 2020) - Bhutia, Sonam Lhamu; Borah, Samarjeet; Pradhan, Ratika; Sharma, Bhushan
Abstract: Landslide can be considered as one of the most common natural threats faced mostly by the people living in the hilly and mountainous regions. Every year, mostly during the monsoons, landslide disrupts the lives of people living in these areas, at times it also leads to the damage of lives, properties etc. Landslide susceptibility mapping has become an essential measure for prevention of losses dues to landslide. In this paper, some input factors that are most common for landslide susceptibility map pertaining to the hilly and mountainous regions have been identified using TF-IDF method.